2020
DOI: 10.1186/s12891-020-03697-1
|View full text |Cite
|
Sign up to set email alerts
|

Early failure for wear after ceramic-on-highly cross-linked polyethylene total hip arthroplasty: a case report

Abstract: Background Highly cross-linked polyethylene (HXLPE) enhances the anti-wear characteristics of the conventional polyethylene (PE). Early failure for wear after ceramic-on-highly cross-linked polyethylene (CoHXLPE) total hip arthroplasty (THA) is extremely rare. Case presentation We described the case of a 60-year-old man who underwent right CoHXLPE THA because of the developmental dysplasia hip (DDH) complained pain 32 months after this procedure. Plain radiographs showed that eccentric wear existed at the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Synderm and others synthesized relevant guidelines and literature and found that if corresponding preventive measures were not taken after hip arthroplasty, DVT confirmed by venography occurred in 30% [ 3 ]. Li and Zhang also showed that the incidence of DVT after hip arthroplasty was 20% without preventive measures [ 4 ]. According to Triantafyllou et al, the probability of DVT after joint replacement is 45% [ 5 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Synderm and others synthesized relevant guidelines and literature and found that if corresponding preventive measures were not taken after hip arthroplasty, DVT confirmed by venography occurred in 30% [ 3 ]. Li and Zhang also showed that the incidence of DVT after hip arthroplasty was 20% without preventive measures [ 4 ]. According to Triantafyllou et al, the probability of DVT after joint replacement is 45% [ 5 ].…”
Section: Literature Reviewmentioning
confidence: 99%